Indonesia has various hardwood species which are known for their low permeability, means difficult to be flown by fluid. The fluid absorption into wood is important especially in preservative treatments, in the treatment before slicing wood sampels for wood anatomy and in wetting air dried wood sampels for specific gravity analyses. The low water absorption of wood are caused by the air presence in cell lumen which could block the water absorption into wood, and anatomy structure of wood itselv - Istie SEKARTINING RAHAYU; Zahrial COTO (Jurnal Ilmu dan Teknologi Hasil Hutan, 2008)
Indonesia has various hardwood species which are known for their low permeability, means difficult to be flown by fluid.  The fluid absorption into wood is important especially in preservative treatments, in the treatment before slicing wood sampels for wood anatomy and in wetting air dried wood sampels for specific gravity analyses. The low water absorption of wood are caused by the air presence in cell lumen which could block the water absorption into wood, and anatomy structure of wood itselves.  One methode to overcome this problem was vacuum treatment. The aim of this research was to increase water absorption in cold water soak methode in 6 wood species (Pterocarpus indicus Willd, Nephelium lappaceum L., Artocarpus heterophyllus Lamk., Paraserianthes falcataria L., Shorea spp,  Dipterocarpus spp) through vacuum treatment.  The size of wood samples were    5 x 5 x 20 cm for cross section orientation, 5 x 5 x 10 cm for radial and tangential orientation with 3 replicants.  These wood samples were treated with 5 different treatments : vacuum treatment for 1 hour and cold water soak process for 24 hours (V), vacuum treatment for 2 hours and cold water soak process for 24 hours (VV), vacuum treatment for 3 hours and cold water soak process for 24 hours (VVV), vacuum treatment for 1 hour, cold wtaer soak for 1 hour, and vacuum treatment again for 1 hour and cold water soak process for 24 hours (VRV), dan vacuum and soaking treatment simultaneously for 5 hours and cold water soak process for 24 hours (VRVRV) and as control, without vacuum treatment, just cold water soak process for 24 hours. The results of this research showed vacuum treatment could increase water absorption.  The highest value of moisture content was obtained at cross section direction in all wood species, followed by tangential and radial direction.  However, every wood species showed different reactions to these five different treatments.   Keywords: